Epidemiological, clinical and histopathological features of meningiomas in a tertiary care hospital - Ali, Kanwar Sajid; Jalal, Malik Liaqat Ali; Hassan, Sohaib; Kashif, Muhammad (International Journal Of Community Medicine And Public Health, 2018)
Background: Meningiomas are the second most common primary tumors of the central nervous system. These tumors have an inherited tendency to progress and recur. These tumors are more common in females. The aim of this study was to observe the epidemiological, clinical and histopathological features of meningiomas in a tertiary care hospital. Methods: This observational study was conducted at the Pathology Department of the Postgraduate Medical Institute (PGMI) Lahore, Pakistan, from January 2013 to December 2013. The cases were collected from the Pathology Laboratory of the Lahore General Hospital, Lahore. This study was conducted on 50 cases of histologically diagnosed meningiomas. The sample size was calculated using 15% expected prevalence of meningiomas at 95% confidence interval and 10% level of precision. Data was entered and analyzed using SPSS version 17. Results: There were 22 (44%) male and 28 (56%) female patients in this study. The mean age of patients was 47.28±14.71 years with the median age 47 years. The minimum and maximum ages were 18 and 75 years and age range was 57 years. Out of 50 cases, fourty two cases were diagnosed as benign meningiomas (WHO Grade-I). Six cases were of atypical meningiomas (WHO grade II). Two cases were diagnosed as anaplastic meningiomas (WHO grade III). Conclusions: It can be concluded from the findings of present study that meningiomas are more common in females than males with grade I meningiomas outnumber the grade II and grade III meningiomas.